Can Neuropeptide S Be an Indicator for Assessing Anxiety in Psychiatric Disorders? - Markiewicz-Gospodarek, Agnieszka; Kuszta, Piotr; Baj, Jacek; Dobrowolska, Beata; Markiewicz, Renata (Frontiers in Public Health, 2022)
Neuropeptide S (NPS) is a neuropeptide primarily produced within three brainstem regions including locus coeruleus, trigeminal nerve nucleus, and lateral parabrachial nucleus. NPS is involved in the central regulation of stress, fear, and cognitive integration. NPS is a mediator of behavior, seeking food, and the proliferation of new adipocytes in the setting of obesity. So far, current research of NPS is only limited to animal models; data regarding its functions in humans is still scarce. Animal studies showed that anxiety and appetite might be suppressed by the action of NPS. The discovery of this neuromodulator peptide is effective considering its strong anxiolytic action, which has the potential to be an interesting therapeutic option in treating neuropsychiatric disorders. In this article, we aimed to analyze the pharmaceutical properties of NPS as well as its influence on several neurophysiological aspects – modulation of behavior, association with obesity, as well as its potential application in rehabilitation and treatment of psychiatric disorders.